Knowledge and attitude of cardiopulmonary resuscitation training and automated external defibrillators training among medical interns in a private medical college - Bhat, Archana; Mahmood, Lulu Sherif; Aroor, Akshatha Rao (Asian Journal of Medical Sciences, 2021)
Background: Knowledge about basic life support (BLS) is mandatory for health-care professionals. Aims and Objectives: This study is done with the objective to evaluate the knowledge about cardiopulmonary resuscitation (CPR) and use of automated external defibrillators (AEDs) among medical students who have completed MBBS course and has enrolled for internship. Materials and Methods: A cross-sectional study using a validated questionnaire was given to MBBS interns before BLS training and same questionnaire was given 1 month after the training. The questionnaire included knowledge and attitudes toward use of CPR and AED and management of choking. Results: Out of the 86 students who answered the questionnaire, the mean score was 11.28 during the pre-test. In the post-test questionnaire, the mean score was 13.91. There was a statistically significant difference (P=0.000) in the post-test scores conducted after 1 month. About 39.6% of students scored average marks (5–10) in the pre-test and 60.4% of students scored good (10–15) marks in the pre-test. After the training session in the post-test, 97.7% of students scored good marks (10–15) while only 2.32% scored average marks. P<0.001, Chi-square=35.97 is highly significant. Conclusion: BLS training helps to increase knowledge of CPR and the use of an AED.